Trehalose dimycolate inhibits phagosome maturation and promotes intracellular Mycobacterium tuberculosis growth via noncanonical SNARE interactions - Carolina Santamaria; Kyle J. Biegas; Pamelia N. Lim; Jessica Cabral; Christi Y. Kim; James R. Lee; Ishani V. Gaidhane; Casey Papson; Kyla Gomard-Henshaw; Alissa C. Rothchild; Benjamin M. Swarts; M. Sloan Siegrist (Proceedings of the National Academy of Sciences, 2025)
Mycobacterial cell envelopes are rich in unusual lipids and glycans that play key roles during infection and vaccination. The most abundant envelope glycolipid is trehalose dimycolate (TDM). TDM compromises the host response to mycobacterial species via multiple mechanisms, including inhibition of phagosome maturation. The molecular mechanism by which TDM inhibits phagosome maturation has been elusive. We find that a clickable, photoaffinity TDM probe recapitulates key phenotypes of native TDM in macrophage host cells and binds several host Soluble N-ethylmaleimide-Sensitive Factor Attachment Proteins Receptor (SNARE) proteins, including Vesicle Transport through Interaction with t-SNAREs 1B (VTI1B), Syntaxin 8 (STX8), and Vesicle-Associated Membrane Protein 2 (VAMP2). VTI1B and STX8 normally promote endosome fusion by forming a complex with VAMP8. However, in the presence of Mycobacterium tuberculosis , VTI1B and STX8 complex with VAMP2, which in turn decreases VAMP8 binding. VAMP2 acts together with mycolate structure to inhibit phagosome maturation and promotes intracellular M. tuberculosis replication. Thus one mechanism by which TDM constrains the innate immune response to M. tuberculosis is via noncanonical SNARE complexation.